Violencias basadas en género: la otra tragedia de Colombia. Indagaciones - Acevedo Valencia, Jenny Marcela (Universidad Católica Luis Amigó, 2021)
This book presents four chapters from completed research dealing with gender-based violence. The first proposes femicide profiles; the second presents cases of economic violence against women; the third proposes an ecological model to explain femicidal behavior; the fourth analyzes different types of gender-based violence towards migrant women. The presentation of these results is expected to contribute to the generation of knowledge and scientific evidence on gender-based violence since this is one of the limitations when proposing plans, policies, and projects to intervene.